Desconstrução mínima e renaturalização : estudo de caso córrego do Aleixo, Barretos-SP - Watanuki Filho, Adhemar (2008)
The interactions of man with nature begin a journey of constant changes in space. Cities as principal product of this process of deconstruction that seeks to analyze and understand in order to establish new forms of interventions concerned with the quality of the place. This practice of deconstruction space is still not understood which ensures the production of spaces marked by the use of the technique. Thus, if one replaces existing nature artificialized by nature. The present study aimed to analyze the perspective of the concepts of deconstruction minimum and the renaturation of Aleixo Stream, the city of Barretos-SP, because it has the attributes necessary to characterize the deconstructions, techniques and common problems that occur in urban streams . To develop the research, the stream in question was divided into five sections, from its source to its encounter with the treatment plant in the city, where aspects of deconstruction were evaluated from the perspective of land use, water and border areas green. Other aspects evaluated were the interventions proposed by the Municipality, with the design of Vale Avenue Fund, that instead of proposing a renaturation replace part of the heritage and border water, with foreclosures, such as point solutions to the problems of urban drainage the municipality. These flooding problems are perhaps an 'alert', instituted by nature, and that can be solved, provided that the anthropic action applied to these spaces is done in a more conscious and socially engaged. To do so, the application of the concepts of deconstruction is the minimum that can ensure the production of balanced spaces. And in cases where the "works" engineering is already consolidated, the use of instruments of intervention as the renaturation becomes essential in the design of more natural environments.